2015
DOI: 10.5455/medarh.2015.69.311-314
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of the Programmed Physical Activities on Lipid Profile in Peripheral Arterial Disease of the Lower Extremities

Abstract: Aims:Determine health effects of programmed physical activities on blood fats in peripheral arterial disease of lower limbs or in examinees on medication therapy and examinees performing programmed physical activities along with the medication therapy.Methods:Overall research has been carried out at the Clinic for Vascular Disease CCUS. Before involvement into the study, examinees had to meet the inclusion criteria. Research was carried out as randomized controlled trial including 100 patients with arterial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…16 The findings was similar to the study conducted by Sahay et al among chickenpox patients in an infectious disease hospital in Mumbai where out of 50 cases majority of participants (79%)belonged to Mumbai and remaining were migrants from West Bengal and Orissa respectively. 20 Study conducted by Pall et al among chickenpox patients in Jharkhand with a sample of 79 cases showed that majority of the participants belonged to the Hindu (96%) religion. 19 Study conducted by Sahay et al among chickenpox patients in an infectious disease hospital in Mumbai where out of 50 cases majority cases (90%) were working as Jari workers and labour in a gold shop.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…16 The findings was similar to the study conducted by Sahay et al among chickenpox patients in an infectious disease hospital in Mumbai where out of 50 cases majority of participants (79%)belonged to Mumbai and remaining were migrants from West Bengal and Orissa respectively. 20 Study conducted by Pall et al among chickenpox patients in Jharkhand with a sample of 79 cases showed that majority of the participants belonged to the Hindu (96%) religion. 19 Study conducted by Sahay et al among chickenpox patients in an infectious disease hospital in Mumbai where out of 50 cases majority cases (90%) were working as Jari workers and labour in a gold shop.…”
Section: Resultsmentioning
confidence: 97%
“…26 24 (20.3%) patients were diagnosed with chronic diseases, remaining 94 (79.7%) were absence of chronic diseases. 20 Out of 118 study subjects, 24 (20.3%) of them were diagnosed with chronic diseases in which diabetes 11 (9.3%) and hypertension 8 (6.6%) were more than bronchial asthma 4 (3.4), allergic rhinitis 1 (0.8) and the remaining 94 (79.7%) were absence of chronic diseases. Varicella vaccination when used as post exposure prophylaxis in children within 5 days of exposure significantly reduces the chance of developing clinical varicella infection.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation